Unpleasant past experience as a determinant of cognitive, behavioral and physiological responses to academic stress in professional examination candidates - de la Fuente, Jesús; Amate, Jorge (Anales de Psicología / Annals of Psychology, 2019)
This investigation established unpleasant past experience in interdependent and predictive relations with irrational beliefs, test anxiety, self-regulated study and academic stress, variables belonging to the competency for performing in highly demanding contexts. Participants were 221 candidates from preparatory academies who were competing for posts as public elementary school teachers. The variables were measured using validated self-reports. A linear, ex post-facto design was used, with inferential and structural analyses. Unpleasant experience was shown to have significant, positive, interdependent relations with irrational beliefs and physiological stress responses, as well as negative relations with self-regulated study. Significant, predictive, structural relations were found between unpleasant experience and cognitive, behavioral, and physiological stress responses. These results partially validate the relationships of the SLPS Competency model, explaining learning in stressful contexts, and offer evidence of the need to train students in these situations.